High Body Mass Index Does Not Adversely Affect Outcomes in High-Level Athletes Undergoing Primary Hip Arthroscopy: A Propensity-Matched Comparison With Minimum 2-Year Follow-up. Issue 2 (February 2022) - Jimenez, Andrew E.; Fox, James D.; Monahan, Peter F.; Lee, Michael S.; George, Tom; Maldonado, David R.; Saks, Benjamin R.; Lall, Ajay C.; Domb, Benjamin G.
Background: The effect of high body mass index (BMI) on outcomes in athletes has not been established. Purpose: (1) To report minimum 2-year patient-reported outcome (PRO) scores and return to sports (RTS) for high-level athletes with high BMI undergoing hip arthroscopy for femoroacetabular impingement syndrome (FAIS) and (2) to compare results with a propensity-matched control group of high-level athletes with a normal BMI. Study Design: Cohort study; Level of evidence, 3. Methods: Data were collected on all professional, collegiate, and high school athletes who had a high BMI (>30) and who had undergone primary hip arthroscopy for FAIS between January 2010 and December 2018. RTS status and minimum 2-year PROs were collected for the modified Harris Hip Score (mHHS), Non-Arthritic Hip Score (NAHS), Hip Outcome Score–Sports Specific Subscale (HOS-SSS), and visual analog scale (VAS) for pain. The percentage of patients achieving the minimal clinically important difference (MCID) and Patient Acceptable Symptom State (PASS) were also recorded. These patients were propensity matched in a 1:3 ratio to high-level athletes with a normal BMI for comparison. Results: A total of 30 high-level athletes with a high BMI were included with a mean follow-up of 49.4 ± 29.5 months. They demonstrated significant improvement from preoperatively to latest follow-up for mHHS, NAHS, HOS-SSS, and VAS ( P < .001). When outcomes were compared with a propensity-matched control group of 90 athletes with a normal BMI, athletes with a high BMI had worse acetabular cartilage injury and were more likely to undergo acetabular microfracture ( P < .001). Athletes with a high BMI demonstrated lower postoperative scores for NAHS when compared with athletes with a normal BMI (88.06 ± 9.37 [range, 60-100] and 90.25 ± 10.79 [range, 48.75-100], respectively; P = .049). Athletes with a high BMI also demonstrated worse postoperative scores for HOS-SSS when compared with athletes with a normal BMI (77.22 ± 18.31 [range, 22.22-100] and 82.38 ± 22.79 [range, 2.78-100], respectively; P = .038). Rates of achieving MCID for the high-BMI and normal-BMI groups were comparable in mHHS (90.0% and 77.8%, respectively; P = .185) and HOS-SSS (90.0% and 82.2%, respectively; P = .397). PASS rates were also comparable between the high- and normal-BMI groups for mHHS (90.0% and 87.8%, respectively; P > .999) and HOS-SSS (70.0% and 71.1%, respectively; P = .908). Athletes with a high BMI also returned to sports at a lower rate compared with athletes with a normal BMI, but this did not reach statistical significance ( P = .479). Conclusion: Athletes with a high BMI undergoing primary hip arthroscopy for FAIS demonstrated significant improvement in PROs and favorable rates achieving clinically meaningful improvement. When compared with a control group of high-level athletes with a normal BMI, they exhibited similar rates of achieving psychometric thresholds and RTS rates. At short-term follow-up, high BMI did not adversely affect outcomes of high-level athletes undergoing primary hip arthroscopy.